2012
DOI: 10.1073/pnas.1203096109
|View full text |Cite
|
Sign up to set email alerts
|

Early-onset binocularity in preterm infants reveals experience-dependent visual development in humans

Abstract: Although there is a great deal of knowledge regarding the phylo- and ontogenetic plasticity of the neocortex, the precise nature of environmental impact on the newborn human brain is still one of the most controversial issues of neuroscience. The leading model–system of experience-dependent brain development is binocular vision, also called stereopsis. Here, we show that extra postnatal visual experience in preterm human neonates leads to a change in the developmental timing of binocular vision. The onset age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
68
2
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(84 citation statements)
references
References 19 publications
12
68
2
2
Order By: Relevance
“…In a series of experiments, Peñ a and colleagues showed that the loss of sensitivity to suprasegmental and segmental features of a foreign language that normally occurs during the first year of life was not dependent on the duration of exposure to broadcast speech (Peñ a et al, 2010(Peñ a et al, , 2012. In contrast, sensitivity to the phonotactic rules of the native language varies with the duration of postnatal experience (Gonzalez-Gomez and Nazzi, 2012), as do a number of visual functions including binocular perception (Jandó et al, 2012) and gaze following (Peñ a et al, 2014). These variations should not be viewed as inconsistent but as pertinent dissociations shedding light on how these computations are realized in vivo.…”
Section: Exploring the Possible Role Of Maturational Tempomentioning
confidence: 87%
“…In a series of experiments, Peñ a and colleagues showed that the loss of sensitivity to suprasegmental and segmental features of a foreign language that normally occurs during the first year of life was not dependent on the duration of exposure to broadcast speech (Peñ a et al, 2010(Peñ a et al, , 2012. In contrast, sensitivity to the phonotactic rules of the native language varies with the duration of postnatal experience (Gonzalez-Gomez and Nazzi, 2012), as do a number of visual functions including binocular perception (Jandó et al, 2012) and gaze following (Peñ a et al, 2014). These variations should not be viewed as inconsistent but as pertinent dissociations shedding light on how these computations are realized in vivo.…”
Section: Exploring the Possible Role Of Maturational Tempomentioning
confidence: 87%
“…The pivotal argument against such a reductionist approach to model anything beyond “simple” plasticity in cultured neuronal networks is the lack of input/interaction of such networks with the environment. However, both plasticity and learning are impacted by environmental stimulation (Callaway and Borrell, 2011; Froemke and Jones, 2011; Henderson et al, 2012; Jando et al, 2012; Young et al, 2012). To address this issue, we compared the overall pattern of developmental signaling in ex vivo neuronal networks in the absence and presence of a model of the onset of sensory input.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, the developmental trajectory of preterm infants was not accelerated by their earlier exposure to speech and face‐to‐face exchange with their parents, suggesting that the external world does not influence the phonetic repertoire during the first weeks of life and thus that learning needs a more mature circuitry reached a few weeks later to stabilize and memorize the external world . Note that other capacities such as binocular perception, gaze following, or sensitivity to the phonotactic rules of the native language are advanced in healthy preterm infants relative to full‐term infants, suggesting a different sensitivity to external stimulation between domains but also within a given processing pathway, owing to different tempos of maturation . These results underscore that, in order to evaluate neonatal care and preterm infant outcomes, it is necessary to precisely evaluate development in terms of cognitive systems and brain networks and not confine studies to general capacities as reflected by IQ.…”
Section: Hello World! Cognitive Processing Of Sensory Informationmentioning
confidence: 98%